Hoping for a cure and planning for end-of-life. Issue 1 (1st June 2011) - Robinson, C
Abstract : Objective: Advance care planning (ACP) aims to enhance end-of-life care yet often fails to live up to that potential. This interpretive study was designed to explore the process and outcomes of ACP using the Patient-centered ACP interview (PC-ACP) developed by Respecting Choices. Method: Patients diagnosed with advanced lung cancer and family members were recruited. Nine family dyads participated in the PC-ACP interview. Follow-up interviews took place 3 and 6 months after the PC-ACP interview. Thematic analysis was conducted on transcribed interviews using constant comparison. Results: Hope was a significant theme in the ACP process and this paper reports on that theme. Hope for a cure was one of many hopes that supported quality of life. Three themes were identified: hope is multi-faceted, hope for a cure is well considered and hope is resilient and persistent. The seeming paradox of hoping for a cure of an incurable cancer did not interfere with the process of ACP. The dyads engaged in explicit discussions of end-of-life scenarios and preferences for care. ACP did not interfere with hope and hope for a cure did not interfere with ACP. Significance: Concerns about false hope are called into question. The principle of honouring hope is not necessarily in conflict with the principle of truthful communication. This is clinically significant as the findings suggest we need not disrupt hope we think of as 'unrealistic' as long as it supports living well. Further, ACP can be successful even in the context of hoping for a cure.